2014
DOI: 10.1353/hpu.2014.0051
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Charges for Asthma-Related Outpatient Visits by Insurance Status

Abstract: Though Americans make 1.8 million asthma-related outpatient visits to the emergency department (ED) annually, little is known about the episodic charges for asthma care in the ED. We therefore sought to assess the bills patients could face for acute asthma incidents by examining hospital charges for asthma-related outpatient ED visits. We performed a nationwide, cross-sectional study of 2.9 million weighted asthma-related outpatient ED visits from 2006–2008 using data from the Medical Expenditure Panel Survey.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Non-controlled asthma results in visits to emergency units and hospital admissions (26) . Despite the guidelines for asthma management, advances in pharmacological treatments and strong evidence of the effects of control medication on the attacks, the number of visits and admissions remains high (27) . This was not observed in the present study, given that higher self-efficacy scores in the scale were associated with better control parameters, as mentioned previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-controlled asthma results in visits to emergency units and hospital admissions (26) . Despite the guidelines for asthma management, advances in pharmacological treatments and strong evidence of the effects of control medication on the attacks, the number of visits and admissions remains high (27) . This was not observed in the present study, given that higher self-efficacy scores in the scale were associated with better control parameters, as mentioned previously.…”
Section: Discussionmentioning
confidence: 99%
“…A study developed in the United States showed that the low-income population affected by asthma faces significant challenges to manage the costs of non-scheduled visits to emergency units. These issues can make families postpone or even give up their search for medical assistance, leading to an attempt to handle the situation at home, which may contribute to a poor prognosis in the treatment of asthma attacks (27) . A study conducted in South Carolina, United States, with 19,512 people, reported that suppression or non-use of control medication is a strong risk predictor for worsening of symptoms and hospital admissions (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Asthma incidence has increased by 15% over the last decade and is a significant and costly public health problem in the United States (Centers for Disease Control and Prevention [CDC], 2011). Asthma exacerbations result in approximately 2 million emergency department (ED) visits annually, with an average cost of $1502 per visit (Wang, Srebotnjak, Brownell, & Hsia, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort study by Hasegawa et al (2014) found that lower socioeconomic status was significantly associated with a higher frequency of ED visits for acute exacerbation of COPD. 6 Similarly, a cross-sectional study of outpatient asthma-related ED visits by Wang et al (2014) identified that the majority of patients in their sample were low-income, defined as ≤ 200% of the federal poverty level. 7 Prescription-related issues after hospital discharge, most often not filling discharge prescriptions, have been found to be especially common among patients with Medicare HMO coverage, Medicaid, or no insurance, and in patients prescribed an inhaler.…”
Section: Introductionmentioning
confidence: 99%
“…6 Similarly, a cross-sectional study of outpatient asthma-related ED visits by Wang et al (2014) identified that the majority of patients in their sample were low-income, defined as ≤ 200% of the federal poverty level. 7 Prescription-related issues after hospital discharge, most often not filling discharge prescriptions, have been found to be especially common among patients with Medicare HMO coverage, Medicaid, or no insurance, and in patients prescribed an inhaler. A patient's medication plan should be developed based on his or her access to resources and consideration of the cost of the medications and interventions.…”
Section: Introductionmentioning
confidence: 99%